THE EFFECT OF PRODUCT DIVERSITY, TOURIST ATTRACTIONS, PRICING AND SERVICE QUALITY MEDIATED BY CUSTOMER SATISFACTION ON TOURIST LOYALTY TO TOURIST ATTRACTION (Case Study on Mbrumbung Market Tourists, Rembang Regency) - Septi Cahya Sari; Syaiko Rosyidi (Jurnal Ekonomi, 2023)
The purpose of this study is to show the influence of product diversity , tourist attractions, pricing, service quality mediated by customer satisfaction on tourist loyalty on tourist attraction (case study on tourists of Pasar Mbrumbung Rembang Regency). This study uses independent variables, namely product diversity , tourist attractions, pricing and service quality, bound variables, namely tourist loyalty and mediation variables, namely customer satisfaction. Data collection techniques were carried out in this study through questionnaires. The source of data used in the research conducted is from primary data sources obtained from research instruments in the form of questionnaires. The population of this study consisted of all tourists who had and/or recently visited Pasar Mrumbung, Rembang Regency. The sampling technique used in the study was non-probability sampling with the sample technique of convenience random sampling, the sample in the study was 100 people who had and/or had just visited the Mbrumbung Market, Rembang Regency. The results showed that tourist attractions and pricing had a significant positive effect on tourist loyalty. Product diversity and service quality have a significant negative effect on tourist loyalty. Product diversity and service quality have a significant positive effect on tourist loyalty mediated by customer satisfaction from the results of the customer satisfaction path analysis test results are able to mediate the effect of product diversity and service quality on tourist loyalty. Tourist attractions have a significant negative effect on tourist loyalty mediated by customer satisfaction from the results of the customer satisfaction path analysis test is unable to mediate the effect of tourist attractions on tourist loyalty. Pricing had no significant negative effect on customer satisfaction-mediated traveller loyalty and from the results of the customer satisfaction path analysis test was unable to mediate the effect of pricing on tourist loyalty.